Novel Saucer-Shaped g-Manganese Dioxides Nanoplates - Zheng, Deshan (Asian Journal of Chemistry, 2012)
g-Manganese dioxides with novel saucer-shaped hexagonal nanoplates structure have been successfully synthesized via a simple chemical route without the addition of any surfactants or organic templates. The hexagonal nanoplates have edge lengths about of 250 nm with the thickness only several tens of nanometers. By tracking the crystallization and morphology of the products at different reaction stages, we proposed a possible formation mechanism of this novel morphology of nanoplates. The present study offered a new, simple route for bulk synthesis of two-dimensional g-MnO2 nanoplates and enlarged the family of MnO2 available.